Measuring the width of growth rings intropical species using digital image processing: the case of retrophyllum rospigliosii - Trullo Guerrero, Ricardo José; Gaviria López, Carlos Alberto; Ramírez Correa, Jorge Andrés (Ingeniería Solidaria, 2025)
Introduction: This article presents the results of the research study "Evaluation of the Correlation Between the Anatomical Characteristics of Colombian Pine Wood (Retrophyllum rospigliosii) Extracted Through Computer Vision and the Climatic Information in the Center of the Cauca Department," conducted as part of a Master’s program in Automation at the University of Cauca in 2023.Objective: To assess the application of artificial vision techniques in measuring the width of growth rings of Retrophyllum rospigliosii.Methods: Twenty cross-sections of Retrophyllum rospigliosii were obtained from plantations located in southwestern Colombia. The sections displayed annual growth rings, and the widths of these rings were measured.Results: In the analyzed cross-sections, 20 annual rings—each corresponding to a year of plantation—were identified. The fully automatic method using a color difference gradient approach yielded a percentage error of 218.05%, detecting only four rings. In contrast, the semi-automatic method successfully identified all 20 growth rings, with an average percentage error of 29.42%.Conclusions: The proposed semi-automatic method for measuring ring width using computer vision demonstrated significantly better performance than the fully automatic approach. The promising results highlight the potential of computer vision tools to identify growth rings and contribute to understanding the climatic history of tropical forests.Originality: A semi-automatic method is proposed for marking and measuring growth rings in the Retrophyllum rospigliosii species.Limitations: The accuracy of ring marking depends on the user’s skill and expertise.